Assessing the gene–disease association of 19 genes with the RASopathies using the ClinGen gene curation framework. Issue 11 (11th October 2018) - Grant, Andrew R.; Cushman, Brandon J.; Cavé, Hélène; Dillon, Mitchell W.; Gelb, Bruce D.; Gripp, Karen W.; Lee, Jennifer A.; Mason‐Suares, Heather; Rauen, Katherine A.; Tartaglia, Marco; Vincent, Lisa M.; Zenker, Martin
Abstract: The RASopathies are a complex group of conditions regarding phenotype and genetic etiology. The ClinGen RASopathy Expert Panel (RAS EP) assessed published and other publicly available evidence supporting the association of 19 genes with RASopathy conditions. Using the semiquantitative literature curation method developed by the ClinGen Gene Curation Working Group, evidence for each gene was curated and scored for Noonan syndrome (NS), Costello syndrome, cardiofaciocutaneous syndrome, NS with multiple lentigines, and Noonan‐like syndrome with loose anagen hair. The curated evidence supporting each gene–disease relationship was then discussed and approved by the ClinGen RASopathy Expert Panel. Each association's strength was classified as definitive, strong, moderate, limited, disputed, or no evidence. Eleven genes were classified as definitively associated with at least one RASopathy condition. Two genes classified as strong for association with at least one RASopathy condition while one gene was moderate and three were limited. The RAS EP also disputed the association of two genes for all RASopathy conditions. Overall, our results provide a greater understanding of the different gene–disease relationships within the RASopathies and can help in guiding and directing clinicians, patients, and researchers who are identifying variants in individuals with a suspected RASopathy. Abstract : The ClinGen RASopathy Expert Panel assessed the published and other publicly available evidence supporting the association of 19 genes with RASopathy conditions using ClinGen's semiquantitative literature curation method. Our group assessed the evidence implicating each gene's association with Noonan syndrome, Costello syndrome, cardiofaciocutaneous syndrome, Noonan syndrome with multiple lentigines, and Noonan‐like syndrome with loose anagen hair. Our results will guide clinicians, patients and researchers in their understanding of the gene‐disease relationships within the RASopathies.